Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/geosciences10100411
|View full text |Cite
|
Sign up to set email alerts
|

Sonar Estimation of Methane Bubble Flux from Thawing Subsea Permafrost: A Case Study from the Laptev Sea Shelf

Abstract: Seeps found offshore in the East Siberian Arctic Shelf may mark zones of degrading subsea permafrost and related destabilization of gas hydrates. Sonar surveys provide an effective tool for mapping seabed methane fluxes and monitoring subsea Arctic permafrost seepage. The paper presents an overview of existing approaches to sonar estimation of methane bubble flux from the sea floor to the water column and a new method for quantifying CH4 ebullition. In the suggested method, the flux of methane bubbles is estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It is significantly lower than the current estimate of its flow, made only for the shelf of the Eastern Arctic seas and amounting to 17 million tons per year [6,52]. At the same time, it was found that the amount of bubble transfer from the bottom sediments of the East Siberian Seas shelf into the water column, depending on the state of the underwater permafrost, changes by five orders of magnitude from 0.001 to 1000 g per square meter per day [49].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is significantly lower than the current estimate of its flow, made only for the shelf of the Eastern Arctic seas and amounting to 17 million tons per year [6,52]. At the same time, it was found that the amount of bubble transfer from the bottom sediments of the East Siberian Seas shelf into the water column, depending on the state of the underwater permafrost, changes by five orders of magnitude from 0.001 to 1000 g per square meter per day [49].…”
Section: Discussionmentioning
confidence: 74%
“…In the context of studies of methane bubble discharge areas using single-beam echo sounders, an expected development is to move from the estimation of the flow of methane into the water to estimates of the flow to the seawater-atmosphere interface. To do this, it is necessary to integrate the coefficients that take into account gas exchange between these bubbles and the liquid column through which they float or develop new methods that take into account this process in the available methods for estimating the amount of methane carried by floating bubbles [6,44,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The ocean is the cradle of life, and it contains many energy sources, including wave energy, coastal tidal energy, estuarine salinity-gradient energy, and submarine volcanic temperature-difference energy. Compared with energy sources that are limited to specific areas, the energy contained in oceanic gas components (bubbles) is a new universal “blue” energy source that is widely present in the ocean . The bubbles present in the ocean mainly come from the decomposition of subsea sediments, , the geological activity of hydrothermal fluids, , cold springs, , and the thawing of permafrost, , and the life activities of marine animals, plants, and microorganisms. , Algae in the sea release large quantities of oxygen into the water through photosynthesis, producing 50% of the oxygen on the earth. , Up to 48 Tg of methane is released annually from subsea sediments . The sound and wave signals caused by the release and rising of subsea bubbles contain important information about subsea geological activities and marine-biological communities; , they are thus important subjects of subsea scientific observations.…”
Section: Introductionmentioning
confidence: 99%
“…5−7 Compared with energy sources that are limited to specific areas, the energy contained in oceanic gas components (bubbles) is a new universal "blue" energy source that is widely present in the ocean. 8 The bubbles present in the ocean mainly come from the decomposition of subsea sediments, 9,10 the geological activity of hydrothermal fluids, 11,12 cold springs, 13,14 and the thawing of permafrost, 15,16 and the life activities of marine animals, plants, and microorganisms. 17,18 Algae in the sea release large quantities of oxygen into the water through photosynthesis, producing 50% of the oxygen on the earth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Three other papers [10][11][12] deal with natural gas seeps in the Arctic shelf. Chernykh et al [10] overview the existing approaches to echo sounding of methane bubble fluxes from the sea bottom into the water and suggest a new technique for quantitative evaluation of methane seepage from the cross section area of a back scattering CH4 bubble plume. The method was successfully tested in single-and multi-beam acoustic surveys of a large seep in the Laptev shelf.…”
mentioning
confidence: 99%